Pengaruh Quality Control Terhadap Efektivitas Proses Produksi - Agnes Dwi Pangestu; Erry Sunarya; Faizal Mulia Z (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The research was aimed at finding out the effect of quality control toward production process effectiveness. The methods used in the research were descriptive and associative methods with quantitative approach. Technique of sampling applied was purposive sampling. Samples in the reserach were staff of production department amounted to 193. Techniques of analyzing data applied were multiple linear regression analysis techniques that included determination coefficients test, multiple correlation coefficient, and partial test (T test). The results found by using determination coefficient test observed from the value of (Adjusted R2 ) is amounted to 0.946 which means that the influence of quality control toward production process effectiveness is aggregated to 94.6%, while the remaining 5.4% is influenced by other factors not explained in the research. Moreover, from the result of correlation coefficient test, the R value observed is amounted to 0.973 showing that there is a very strong relationship between quality control and production process effectiveness. Keywords: Quality Control, Production Process Effectiveness, Garment Industry